The Non-Partition of Sindh - Kataria, Shyamal (Advances in Social Sciences Research Journal, 2024)
While Partition can indeed be viewed as a tragedy of epic proportions for anyone that has a belief in common humanity, it is undoubtedly the case that certain groups were more impacted by it than others, both materially and psychologically. This article will focus on one such group, the Hindu Sindhis, who, unlike most other non-Muslims that fled the territories of would-be/realised Pakistan, did not have a linguistically similar destination within rump India to migrate to. Indeed many Hindu Sindhis lament the fact that they lost their entire province to Pakistan. Taking this into view, this article will attempt to tackle the question of whether the partition of Sindh, along the lines implemented in certain other provinces of British India, was a legitimate option at the time to lobby for.